2015
DOI: 10.1175/jamc-d-14-0072.1
|View full text |Cite
|
Sign up to set email alerts
|

Variability of CONUS Lightning in 2003–12 and Associated Impacts

Abstract: Changes in lightning characteristics over the conterminous United States (CONUS) are examined to support the National Climate Assessment (NCA) program. Details of the variability of cloud-to-ground (CG) lightning characteristics over the decade 2003-12 are provided using data from the National Lightning Detection Network (NLDN). Changes in total (CG 1 cloud flash) lightning across part of the CONUS during the decade are provided using satellite Lightning Imaging Sensor (LIS) data. The variations in NLDN-derive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 66 publications
2
66
0
2
Order By: Relevance
“…A cloud-to-ground flash has one or more return strokes, and the NLDN reports both CG flashes and CG strokes, as well as some fraction of cloud pulses within both CG flashes and cloud flashes (those without return strokes). Orville and Silver (1997) 1992-95 CONUS First multiyear CONUS map Zajac and Rutledge (2001) 1995-99 CONUS Updated multiyear CONUS map Orville et al (2002) 1998-2000 CONUS and Canada Added Canada to CONUS Orville (2008) 1998-2000 CONUS History of NLDN in CONUS Rudlosky and Fuelberg (2010) 1996-2001 vs 2004-09 CONUS NLDN upgrade impacts Orville et al (2011) 2001-09 CONUS and Canada Annual and multiyear maps Holle (2014) 2005-12 CONUS Diurnal variations Koshak et al (2015) 2003-12 CONUS 10-yr climatology…”
Section: Lightning and Severe Weather Datamentioning
confidence: 99%
See 1 more Smart Citation
“…A cloud-to-ground flash has one or more return strokes, and the NLDN reports both CG flashes and CG strokes, as well as some fraction of cloud pulses within both CG flashes and cloud flashes (those without return strokes). Orville and Silver (1997) 1992-95 CONUS First multiyear CONUS map Zajac and Rutledge (2001) 1995-99 CONUS Updated multiyear CONUS map Orville et al (2002) 1998-2000 CONUS and Canada Added Canada to CONUS Orville (2008) 1998-2000 CONUS History of NLDN in CONUS Rudlosky and Fuelberg (2010) 1996-2001 vs 2004-09 CONUS NLDN upgrade impacts Orville et al (2011) 2001-09 CONUS and Canada Annual and multiyear maps Holle (2014) 2005-12 CONUS Diurnal variations Koshak et al (2015) 2003-12 CONUS 10-yr climatology…”
Section: Lightning and Severe Weather Datamentioning
confidence: 99%
“…Following the upgrade in 2013, this DE increased to about 50% (Nag et al 2014;Murphy and Nag 2015). Koshak et al (2015) provided more details about the time evolution of NLDN performance before 2012. Definitions and context for these lightning performance measures are provided in Nag et al (2015).…”
Section: Lightning and Severe Weather Datamentioning
confidence: 99%
“…Incorporating chemical transport modeling may improve this filter. Moreover, the results presented here represent an alternative and indirect way to assess the importance of lightning NOx for National Climate Assessment (NCA) analyses 15 described in Koshak et al (2015), and Koshak (2017). Inversion studies (e.g., Zhao and Wang, 2009;Gu et al, 2013Gu et al, , 2014Gu et al, , 2016 will be needed to understand the emission changes corresponding to the OMI tropospheric NO2 VCD trends.…”
Section: Discussionmentioning
confidence: 99%
“…The lightning trend in the NLDN data is unclear due in part to the changing instrument sensitivity (Koshak et al, 2015). If lightning NOx is not accounted for in OMI retrieval, tropospheric NO2 VCDs are overestimated.…”
Section: Omi-based No2 Trendsmentioning
confidence: 99%
“…Romps et al (2014) suggested that the lightning flash rate is proportional to the convective available potential energy (CAPE) times the precipitation rate and, when applied to 11 climate models, CONUS lightning strikes were predicted to increase 12 ± 5% per degree Celsius of warming. Using 2003-2012 cloud-to-ground lighting data across the U.S. from the National Lightning Detection Network (NLDN), Koshak et al (2015) found a 12.8% downward trend in total cloud-to-ground lightning count for the 10-year period, although the authors found a slow upward trend in the number of positive-polarity flashes. This was during a time when temperatures were warming but moisture trended downward.…”
Section: Outlooks Into the Futurementioning
confidence: 99%